Pemanfaatan Media Pemasaran Dalam Meningkatkan Brand Awareness Toko Roti MM di Kota Medan - Lailaty, Khaira Ma’rifa (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
The importance of media in disseminating information in the business world, where being known will win the market, but if unknown will lead to bankruptcy. This research aims to provide an overview of the utilization of marketing media used by MM Bakery in Medan City to increase brand awareness. In this study, the relevant theories are Marketing Communication, Marketing Media, and Brand Awareness. The research method used is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. The analysis techniques used include data reduction or sorting, data presentation, conclusion drawing, and verification. The research informants consist of company leaders, company public relations, and an employee. The results of the study show that MM Bakery uses various marketing strategies, such as social media, direct communication, and participation in events, to increase their brand awareness in Medan City. They also focus on product quality, excellent service, and responsiveness to customers to build loyalty and receive positive responses from the public